ANALISIS SENTIMEN ULASAN APLIKASI WATTPAD DI GOOGLE PLAY STORE DENGAN METODE RANDOM FOREST - Safira Nur Adhan; Gusti Ngurah Adhi Wibawa; Dian Christien Arisona; Irma Yahya; Ruslan Ruslan (Program Studi Ilmu Komputer FMIPA-UHO, 2024)
Wattpad is an application and online community site that allows users to write or read informational content in the literary sphere with various genres or categories such as short stories, classics, action, adventure, romance, fantasy, humor, spiritual, mystery, horror, poetry, science fiction, historical fiction, teen fiction, general fiction, fan fiction, and non-fiction. By December 2023, 90 million users spent more than 23 billion minutes accessing the app each month. This study aims to provide an overview of user sentiment while classifying it as negative or positive sentiment text using Random Forest and Random Forest methods optimized with the SMOTE (Synthetic Minority Oversampling Technique) on Wattpad App user reviews that experience class imbalance. The results showed that out of 9.975 data collection results, only 8.743 data could be used with a percentage of positive sentiment of 64,2% (5.616) and 35,8% (3.127) negative sentiment. The Random Forest method without SMOTE optimization tends to be superior in predicting unbalanced sentiment classification, this can be seen from the accuracy value which reaches 84,05%, precision 84,71%, recall 91,60%, F1-Score 88,02%, FPR 8,40%, and AUC value 0,9166 are categorized as excellent classification. SMOTE Random Forest modeling is able to improve the ability to classify the minority class, negative sentiment, as can be seen from the increase in precision value from 84,71 % to 86,70% (1,99%). Unfortunately, this class balancing resulted in a decrease in the performance of accuracy, recall, f1-score and AUC values. In addition, based on the feature importance values, the most influential features in both models are the word attributes